Designing the Infrastructural Model for Smart Hospitals in Iran; a Mixed-Methods Approach - Layeghi-Ghalehsoukhteh, Tayebe; Hessam, Somayeh; Mahfoozpour, Soad; Vahdat, Shaqayegh (Archives of Men’s Health, 2023)
Introduction: The smartification of hospitals has the potential to enhance the quality of services, ensuring faster and more efficient healthcare delivery while improving the tracking and security of hospital equipment. We aimed to design an infrastructural model for smart hospitals in Iran. Methods: A mixed-methods approach was used combining qualitative Grounded Theory and quantitative descriptive-survey methods. The qualitative phase involved in-depth semi-structured interviews with 12 experts familiar with hospital smartification concepts. In the quantitative segment, 412 participants, including senior healthcare managers, IT specialists, hospital administrators, technology experts, and university faculty members, were surveyed using a structured questionnaire. Statistical analyses, including Kolmogorov-Smirnov and independent t-tests, were conducted, and a structural equation model was developed using SPSS 21 and LISREL 8.5 software. Results: In the qualitative phase, 135 initial codes and 22 subcategories were identified, eventually consolidated into six main categories: information and communication infrastructures, advanced medical technologies, hospital management, trained human resources, financial resources, and monitoring and control systems. The highest coefficient belonged to the information and communication infrastructures (F1) with a value of 94.3, while the lowest was related to monitoring and control (E5) with a value of 65.0, all indicating significant relationships among the dimensions of hospital smartification. Conclusion: Based on the findings, information and communication infrastructures; advanced medical facilities and technologies; human resources; management; monitoring and control systems; and financial resources were identified and validated as six main infrastructures of smart hospital in Iran.